Structure and Seasonal Variability of the Arctic Boundary Current North of Severnaya Zemlya. Issue 1 (21st January 2023) - Ruiz‐Castillo, Eugenio; Janout, Markus; Hölemann, Jens; Kanzow, Torsten; Schulz, Kirstin; Ivanov, Vladimir
Abstract: We assessed the spatial and temporal variability of the Arctic Boundary Current (ABC) using seven oceanographic moorings, deployed across the continental slope north of Severnaya Zemlya in 2015–2018. Transports and individual water masses were quantified based on temperature and salinity recorders and current profilers. Our results were compared with observations from the northeast Svalbard and the central Laptev Sea continental slopes to evaluate the hydrographic transformation along the ABC pathway. The highest velocities (>0.30 m s −1 ) of the ABC occurred at the upper continental slope and decreased offshore to below 0.03 m s −1 in the deep basin. The ABC showed seasonal variability with velocities two times higher in winter than in summer. Compared to upstream conditions in Svalbard, water mass distribution changed significantly within 20 km of the shelf edge due to mixing with‐ and intrusion of shelf waters. The ABC transported 4.15 ± 0.3 Sv in the depth range 50–1, 000 m, where 0.88 ± 0.1, 1.5 ± 0.2, 0.61 ± 0.1 and 1.0 ± 0.15 Sv corresponded to Atlantic Water (AW), Dense Atlantic Water (DAW), Barents Sea Branch Water (BSBW) and Transformed Atlantic Water (TAW). 62–70% of transport was constrained to within 30–40 km of the shelf edge, and beyond 84 km, transport increases were estimated to be 0.54 Sv. Seasonality of TAW derived from local shelf‐processes and advection of seasonal‐variable Fram Strait waters, while BSBW transport variability was dominated by temperature changes with maximum transport coinciding with minimum temperatures. Further Barents Sea warming will likely reduce TAW and BSBW transport leading to warmer conditions along the ABC pathway. Plain Language Summary: We assessed the structure and seasonal variability of the flow and water masses of the Arctic Boundary Current (ABC) in the region north of Severnaya Zemlya. This current is important in the Arctic Ocean as it transports relatively warm and saline waters along the Eurasian Arctic continental slope. We quantified the flow, transport and hydrographic variability of the ABC. Compared to observations from upstream, our results indicate that the water masses away from the shelf break maintained the hydrographic characteristics from upstream. In contrast, the water masses near the shelf break were significantly cooled and freshened due to intrusion of‐ and mixing with shelf waters. The water masses near the shelf break showed a seasonal signal in volume transport and temperature which derives from local shelf processes, advection of seasonal‐variable waters along the ABC pathway and the seasonal cooling of the Barents Sea. If the warming trend in the Barents Sea continues, warmer waters are expected to be advected eastward along the Eurasian continental slope by the ABC. Key Points: We quantify the Arctic Boundary Current (ABC) transport north of Severnaya Zemlya with a 2015–2018 mooring array Hydrographic changes along the ABC pathway are most prominent at the continental slope due to the interaction with shelf water Seasonality of water masses from the shelf sea was observed in transport, temperature and off‐shelf excursions within the ABC